Synthesis Gas Production From Palm Oil Shell Waste Using Al/Cr Metal Pillared Bentonite Catalyst For Eco-Friendly Fuel - Indah Puspita; Muhammad Faizal; David Bahrin (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2024)
The production of palm oil shell waste in the palm oil industry is increasing, but the utilization of palm oil shell waste has not been utilized optimally. Palm Oil Shells must be processed and utilized to reduce pollution and increase the use value of waste. This research aims to utilize palm oil shell waste using an Al/Cr metal pillared bentonite catalyst with a gasification process to produce synthesis gas. The bentonite pillarization process using Al/Cr metal aims to increase the catalyst surface area, basal distance and catalyst surface acidity so as to increase the catalytic activity of the catalyst in the gasification process. The gasification process is carried out at temperatures of 450, 500, 550 and 600°C. Adding the Al/Cr metal pillared bentonite catalyst, the H2 concentration increased significantly. The effect of increasing temperature can increase the H2 content by consuming CO within a certain time limit. The gasification process at temperature 600°C with a 20% Al/Cr metal pillared bentonite catalyst is the optimal condition for producing synthesis gas. The heating value of the gasification results in terms of the optimum HHV and LHV values is 16.21 MJ/Nm3 and 14.59 MJ/Nm3. Based on research, gasification of palm oil shells using an Al/Cr metal pillared bentonite catalyst is feasible for the production of environmentally friendly fuel